Development of Quantity and Quality of Organic Granule Fertilizer Products in Home Industries - Susi Nurweni; Vincentius Supriyono; Beny Suyanto (Alliance oh Health Activists (AloHA), 2021)
This research is a development of previous research (2018) on the manufacture of granulated organic fertilizer. The purpose of this research is to make compost into organic fertilizer granules. To speed up composting, MOL is used. This study applied a factorial design with a factor of type of adhesive and a factor of the percentage of adhesive added. The adhesive consisted of 3 types, namely clay and molasses, while the comparison factor for the percentage of adhesive consists of 3 levels, namely 5%; 7.5% and 10%. Each treatment variation was replicated 5 times. The results showed that the bulk density was 0.4-0.6 g/cm3, the percentage of granule size was 70%-85%, water absorption was 29%-36% and the dispersion time was 13-22 hours. The levels of N = 3.48%-8.53%, P = 1.30%-2.03%, K = 0.03%-6.73% and C/N ratio = 12.92-20.45. Furthermore, it was concluded that the C/N ratio, N, P and K granules of organic fertilizer produced had met the requirements of the Regulation of the Minister of Agriculture of the Republic of Indonesia No. 70/Permentan/SR.140/10/2011. Keywords: compost; granule organic fertilizer; granulator